Overview of the Infection Control Prevention Program in the Internal Room of Aloei Saboe Hospital, Gorontalo City - Sabirin B Syukur; Rini Asnawati; Moh. Sudirman Mustapa; Siti Rahma Binol; Nurdawati Lajambu; Ni’ma Chusnul Chatimah; Nolva Laiya (Journal of Community Health Provision, 2022)
Infection Prevention and Control (PPI) is an endeavor to prevent and reduce the incidence of infections among patients, employees, visitors, and members of the community in health care institutions. In order to reduce the occurrence of nosocomial infections, nosocomial infection control involves planning, implementing, monitoring, and encouraging. This study's objective was to characterize infection prevention and control in the interior chamber of Prof. Dr. Aloei Saboe Gorontalo City. This study employed a qualitative descriptive research approach with a random sample of 15 participants. The results indicated that the infection prevention and control program in the internal room had not been fully implemented, as 3 of the 15 participants did not practice proper handwashing (i.e., they did not follow the 6 steps outlined in the standard operating procedure), 1 participant did not use PPE during the procedure, but was able to apply coughing and sneezing etiquette, and 1 participant did not follow safe injection practices. Decontamination of equipment following completion of actions.